Managing Innovational Processes at Cotton Processing Enterprises in Central Asia Countries - Mombekova, Gulmira; Turysbekova, Gulzhan; Baimbetova, Assel (International Journal of Economics and Financial Issues, 2016)
Cotton is the most important cash crop in the economy of the Central Asia countries. After the Central Asia countries acquired their independence, decisive steps have been taken to liquidate the dependence on the export of cotton fiber and to increase volumes of cotton processing. At the present time the Central Asia countries have achieved a definite success in the development of cotton processing industry: new plants have been constructed and put into service, and the current production facilities have been modernized. However, productive capacities and technological level of cotton processing enterprises do not make it possible to turn out competitive products with the high added value. The situation in the cotton processing industry of the Central Asia countries emphasizes the urgency to increase the productivity, quality and competitiveness of products of cotton processing by forming a national innovative system of the industry development. The analysis of the positions of the Central Asia countries on the world cotton market and peculiarities of the development of cotton processing industry in the region allowed the author to make the conclusion that mastering and applying innovational technologies are a necessary condition for ensuring competitive advantages for cotton processing enterprises. The conducted research demonstrates that national systems of the Central Asia countries do not fully comply with the needs of the cotton processing industry and at the present time they are at their stages of formation. The author offers the following measures as basic ones in order to increase innovational activity of enterprises of cotton processing industry of Central Asia countries: increasing expenses for R&D, implementing reforms of innovative systems, modernizing systems of higher education, raising external investments for the development of the sectoral science, and developing and implementing mechanisms to support innovational entrepreneurship. Keywords: cotton cultivation, textile industry, competitiveness, innovations JEL Classifications: E22, O13